NF-κB signaling regulates myelination in the CNS - Blank, Thomas; Prinz, Marco (Frontiers in Molecular Neuroscience, 2014)
Besides myelination of neuronal axons by oligodendrocytes to facilitate propagation of action potentials, oligodendrocytes also support axon survival and function. A key transcription factor involved in these processes is nuclear factor-κB (NF-κB), a hetero- or homodimer of the Rel family of proteins, including p65, c-Rel, RelB, p50, and p52. Under unstimulated conditions, NF-κB remains inactive in the cytoplasm through interaction with NF-κB inhibitors (IκBs). Upon activation of NF-κB the cytoplasmic IκBs gets degradated, allowing the translocation of NF-κB into the nucleus where the dimer binds to the κB consensus DNA sequence and regulates gene transcription. In this review we describe how oligodendrocytes are, directly or indirectly via neighboring cells, regulated by NF-κB signaling with consequences for innate and adaptive immunity and for regulation of cell apoptosis and survival.